Prevalence of obesity among the school going adolescents in urban Bangalore - Dr. Niranjan H S; Dr. Nijaguna N; Dr Ganesh Kamath (Pediatric Review: International Journal of Pediatric Research, 2015)
Background: Obesity, one of the most widespread and major problems affecting children and adolescents is of global nutritional concern. We conducted this study to estimate the prevalence of obesity among urban Bangalore school going adolescents.Material and Methods: School based cross-sectional study was conducted in schools in Bangalore during December 2012 to November 2013. The students were given a pre-designed structured questionnaire which consisted of questions to be answered by the student, with the help of his/her parents at home. Anthropometric measurements were taken to determine the prevalence of obesity.Results: This was an observational study consisting of 748 children is undertaken to study the prevalence of obesity. Prevalence of obesity in adolescents was found to be 5.9% in the present study. Prevalence of obesity was highest among in 15 year old adolescents (9.3%) as compared to the overall prevalence of 5.9% (p = 0.039). The prevalence of obesity among adolescents had a birth weight >3.5kg was 10.7% (p= 0.069). Among obese adolescents, 79.5% had mixed diet pattern. Among adolescents with family history of obesity, 22.9% were obese as compared to 4.1% prevalence of obesity among adolescents without family history of obesity. Majority of obese adolescents belonged to upper middle class socioeconomic status (9.6%) (p = 0.028).Conclusion: There is a significant prevalence of obesity among adolescents of urban Bangalore. Mixed diet, upper middle class SES and family history of obesity have a strong correlation with the prevalence of obesity in adolescents.